Long‐Run Performance following Private Placements of Equity - Hertzel, Michael; Lemmon, Michael; Linck, James S.; Rees, Lynn (Journal of Finance, 2002)
Public firms that place equity privately experience positive announcements effects, with negative post‐announcement stock‐price performance. This finding is inconsistent with the underreaction hypothesis. Instead, it suggests that investors are overoptimistic about the prospects of firms issuing equity, regardless of the method of issuance. Further, in contrast to public offerings, private issues follow periods of relatively poor operating performance. Thus, investor overoptimism at the time of private issues is not due to the behavioral tendency to overweight recent experience at the expense of long‐term averages.